The use of different levels of mulberry leaf meal with the broken-riceberry-based diet for semi-free range layers - Chalermsan, Nitima (Journal of Science and Agricultural Technology, 2021)
The present study investigated the effect of semi-free range laying hen fed dietary mulberry leaf meal mixed plus broken riceberry on egg performance, egg quality, and health. A randomized complete block experimental design was assigned, which block was a housing model (sunshine and shade). One hundred sixty laying hens (59 weeks of age) were divided into four groups in each house (20 birds of each group). The laying hens in each group were randomly assigned to 4 dietary treatments as follows: Diet 1, 2, 3, and 4, which were used broken riceberry as an energy source and mixed with 0, 2, 4, and 6 % sun-dried mulberry leaf meal, respectively. There were two consecutive 28 day periods to collect data based on egg production and egg quality. In the last period, the feces of each group were randomly collected to determine the number of microorganisms (total plate count, coliform, salmonella, and lactic acid bacteria). The results showed that there were no statistical differences among the four groups on egg production percentage, daily feed intakes, feed conversion ratio per 1 kilogram of egg weight, feed cost per 1 kilogram of egg weight, egg weight, albumen height, haugh unit, eggshell thickness, and the number of coliforms and lactic acid bacteria in feces (P>0.05). However, the egg yolk color scores were the highest, followed by diet 3, 2, and 1, respectively (P<0.05). The total plate count and salmonella in the feces of the laying hen fed with diet 4 were the lowest (P<0.05). In addition, feed cost per 1 kilogram of egg weight of the group fed with diet 4 was slightly lower than other groups.